2020
DOI: 10.22452/mjlis.vol25no2.2
|View full text |Cite
|
Sign up to set email alerts
|

Research data management policies in USA, UK and Australia universities: An online survey

Abstract: There has been an increase in demand for research data management (RDM) policies to improve the quality of research data however, there is no clear-cut policy content to guide the process. The purpose of this study is to identify the existing RDM policies. Specifically, the study compares and differentiates the RDM policies in three developed nations (USA, UK and Australia) to ascertain how the policies vary. The RDM policies of 100 universities from the three countries, that are present online were retrieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…So, the questions are related to their roles and support services in RDM. Previous finding in Liu et al (2020), Research data management policies in USA, UK and Australia universities has demonstrated the areas of focus of research data management policies and the stakeholders' roles and its intended benefit. Therefore, the researchers' work was measured with RDM support received, and their roles in RDM such as data sharing and access and DMP data and data analysis.…”
Section: Instrumentationmentioning
confidence: 96%
See 1 more Smart Citation
“…So, the questions are related to their roles and support services in RDM. Previous finding in Liu et al (2020), Research data management policies in USA, UK and Australia universities has demonstrated the areas of focus of research data management policies and the stakeholders' roles and its intended benefit. Therefore, the researchers' work was measured with RDM support received, and their roles in RDM such as data sharing and access and DMP data and data analysis.…”
Section: Instrumentationmentioning
confidence: 96%
“…According to Liu et al (2020), in the USA, UK, and Australia, data sharing, data management plan, access, and retention are critical requirements from funders as conditions to access research grants. The authors found that there is no difference in these countries regarding RDM.…”
Section: Introductionmentioning
confidence: 99%
“…RDM development strategies such as RDM policies, infrastructure, resources and capacity-building programmes are truly required in a university to effectively manage data for a better understanding of its lifecycle, availability, accessibility, security, use and re-use. Unfortunately, Liu et al . (2020, p. 21) observed RDM policies as still in their initial stages in many countries, and most universities have either full or partial solutions in place.…”
Section: Theory and Literature Reviewmentioning
confidence: 99%
“…Policies should serve the needs of the different research disciplines. Moreover, they should be open enough to respond to technical or discipline changes as well as to ensure research freedom (Liu et al, 2020;Schmidt and Dierkes, 2015). Data policies of journals or funders will influence the data handling of the researchers and need to be considered in the development process of an institutional policy Higman and Pinfield, 2015).…”
Section: Policies/guidelinesmentioning
confidence: 99%